BENDING STRENGTH AND STIFFNESS OF POLES OF ARGENTINEAN Eucalyptus grandis - E.A Torrán; M.A Sosa Zitto; A.D Cotrina; J.C Piter (Maderas: Ciencia y Tecnología, 2009)
The present paper reports the results of an investigation regarding the determination of bending strength and stiffness in full-size poles of Argentinean Eucalyptus grandis. The importance of accurately knowing the mechanical properties of this material has increased with the increasing demand of utility poles of this species and with the use of modern procedures aimed at achieving a reliable and economical structural design. For this purpose an empirical research project with two samples containing new, green, untreated poles was carried out according to the procedures adopted by both the American standard ASTM D 1036 (2005) and the Argentinean standard IRAM 9529 (2004) for cantilever bending tests. Sample 1 enclosed 14 year-old poles with nominal length of 12 m and Sample 2 enclosed 11 year-old poles with nominal length of 8 m. The results found for the average circumference taper were similar to the values adopted by the American standard ANSI 05.1 (2002) and knot dimensions as well as knot ratio compared well with those permitted by this standard. The mean value found for maximum fibre stress at ground line reached 62.9 N/mm² for Sample 1 and 56.3 N/mm² for Sample 2. These strength results are relatively high in comparison with values reported for seasoned sawn timber of the same species and they compare well with those published by the American standard ANSI 05.1c (2004) for poles of different species. Both samples showed a coefficient of variation of 13 % for strength at ground line which is relatively low in comparison with those adopted by the American standard and may be considered an advantage of this material for structural purposes. The mean value found for modulus of elasticity reached 10935 N/mm² for Sample 1 and 9546 N/mm² for Sample 2, with a coefficient of variation of 14 % for both cases. Results also revealed significant differences between mechanical properties values corresponding to the two samples containing poles with different sizes and age. The correlation coefficient between knot ratio and strength showed the insignificant values of 0.09 and 0.02 for Sample 1 and 2 respectively, and the corresponding results between modulus of elasticity and strength were 0.52 and 0.37. En el presente trabajo se presentan los resultados de una investigación orientada a determinar la resistencia y la rigidez de postes de Eucalyptus grandis de Argentina. La importancia de conocer con precisión las propiedades mecánicas de este material cobró mayor relevancia con la creciente demanda de postes de esta especie y con la adopción de modernos procedimientos de cálculo orientados a lograr un diseño estructural confiable y económico. Con este fin se llevó a cabo un proyecto empírico que abarcó dos muestras de postes en tamaño estructural, nuevos y sin tratamientos, los cuales se ensayaron en estado verde conforme a los procedimientos establecidos en la norma estadounidense ASTM D 1036 (2005) y en la argentina IRAM 9529 (2004) para pruebas en voladizo. La muestra 1 incluyó postes con 12 m de longitud nominal y una edad de 14 años, y la muestra 2 estuvo compuesta por postes con 8 m de longitud nominal y una edad de 11 años. Los valores promedio encontrados para la conicidad fueron similares a los adoptados por la norma ANSI 05.1 (2002) y tanto el tamaño de los nudos como la nudosidad compararon bien con los valores permitidos por esta norma. El valor medio de la tensión de rotura en la línea de empotramiento fue de 62,9 N/mm² para la Muestra 1 y de 56,3 N/mm² para la Muestra 2. Estos resultados son relativamente altos en comparación con los publicados para madera aserrada de la misma especie ensayada en estado seco y son comparables a los adoptados por la norma ANSI 05.1c (2004) para postes de diferentes especies. Ambas muestras exhibieron un coeficiente de variación de 13 % para la resistencia en la línea de empotramiento, valor que es relativamente bajo en comparación con los adoptados por la norma estadounidense y puede ser considerado una ventaja del material para uso estructural. El valor medio del módulo de elasticidad alcanzó 10935 N/mm² para la muestra 1 y 9546 N/mm² para la muestra 2, con un coeficiente de variación de 14 % en ambos casos. Los resultados también pusieron de manifiesto diferencias significativas entre los valores de las propiedades mecánicas de ambas muestras, integradas por postes de diferentes edades y dimensiones. El coeficiente de correlación entre la nudosidad y la resistencia alcanzó los insignificantes valores de 0,09 para la muestra 1 y de 0,02 para la muestra 2, mientras que los valores correspondientes entre el módulo de elasticidad y la resistencia fueron 0,52 y 0,37.